A Novel Ratiometric Fluorescent Probe for Hypobromous Acid Detection in Living Cells. Issue 40 (25th October 2022) - Zhang, Jin; Liu, Saiwen; Liu, Changhui; Hu, Yongjun; Peng, Tianying; He, Yiyun
Abstract: A novel ratiometric fluorescent probe HB‐2 based on benzothiazole for hypobromous acid (HBrO) was synthesized and studied. After HBrO was added to the CH3 CN‐HEPES solution of the HB‐2, the probe cyclized to form a sulfimine bond, which increased the conjugated degree of the system. The fluorescence emission peak of the reaction system at 447 nm gradually decreased, while the newly generated emission peaks gradually increased at 580 nm. The ratio of the fluorescence intensity at the two wavelengths of 447 nm and 580 nm increased about 234 times. Moreover, it has successfully been used to stain and record microscopy images of 4T1 cells, and the presence of exogenous HBrO could be judged by the change of fluorescence intensity. Abstract : The fluorescence of compound HB‐2 itself has blue fluorescence, after HBrO was added to the solution of compound HB‐2, the color of the solution changed obviously from yellow to orange. And cell images were taken through two collection channels in 4T1 cells, the color brightness changed from blue to red.